Students' Acceptance Level of Augmented Reality Technology Applied to Teaching Tools Chiller Simulation System - Kamarolzaman, Nurul Fitrah; Razali, Nizamuddin; Abdul Jalil, Muhammad Zuhairi; Ismail, Mohd Erfy; Hashim, Suhaizal; Abdul Rahman, Khairul Anuar (Online Journal for TVET Practitioners, 2023)
Along with the development of technology, Augmented Reality (AR) has been used as a teaching aid to facilitate the teaching and learning process. Nevertheless, the use of AR technology in teaching and learning session in Vocational College is still at a minimal level. Therefore, this study was conducted to identify the level of students' acceptance of AR technology from the aspects of perceived usefulness, perceived ease of use and attitude. A total of 114 students who took the Diploma in Refrigeration and Air Conditioning (PPU) program at Batu Pahat Vocational College, Kluang Vocational College, Muar Vocational College and Segamat Vocational College were involved in this study. The distribution of the questionnaire for this study is using google form through the online platform. This study uses descriptive analysis method (mean and standard deviation). The reliability value for this study instrument is ? = 0.890. Overall, the results of the study showed that the level of perceived usefulness, the level of perceived ease of use and the level of attitude were at a high level with a mean value (M = 4.34, M = 4.36, M = 4.25). In conclusion, the results of this study indicate that most students have a high level of acceptance of the use of AR technology in teaching and learning session. In this regard, Vocational College should strive to enhance the use of AR technology so that the teaching and learning process can be carried out more effectively.